An assessment of the feasibility to extend contributory social security scheme to the informal sector by National Social Security Authority - Tererai, Simukai Betserai Freedom (Midlands State University, 2019)
Authority (NSSA) to extend contributory social security scheme to the informal sector. The research was motivated after realizing that the informal sector in Zimbabwe is increasing at the expense of formal sector which is leading to the contribution base of NSSA to decrease since only formally employed workers are the ones who are obliged to contribute. This leads to a funding gap where contributions are declining whilst claims are increasing hence the need to extend social security to the informal sector so as to maintain viability of the scheme. The study analyzed the willingness of informal sector to contribute to the scheme, the challenges that can be encountered by NSSA in extending the scheme as well as the strategies that were used by other countries in extending social security to the informal sector. A descriptive research design was used on this study. The sample size of sixty informal sector workers and five NSSA personnel was selected making it a total of sixty-five. Both primary and secondary data was used. The data was collected through questionnaires, interviews and published reports. The study established that there is a significant number of people who are willing to contribute to the scheme, there are challenges which can be encountered in extending contributory social security to the scheme which include lack of trust to the scheme by informal sector workers, lack of their capacity to contribute as well as administrative costs. Other countries also were successful in extending social security to the informal sector through use of different strategies. Considering the results found it can be feasible for NSSA to extend the scheme to informal sector. The study recommended the policy makers to put a policy that allow informal sector to contribute to the scheme, also it was recommended that NSSA should venture into awareness campaigns to increase knowledge on contributions and benefits. The study continued to recommend for implementation of flexible contributions which can allow everyone to be able to pay as well as putting payment methods which are convenient to the informal sector workers.